KAJIAN FILOSOFI PEMENTASAN REOG PONOROGO DI KABUPATEN PONOROGO JAWA TIMUR (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Reog Ponorogo is a traditional art from the Ponorogo region that has been passed down fromgeneration to generation and contains noble cultural values. This study discusses the role ofReog Ponorogo performing arts as a medium to gain mass support and its relation to politicalconditions in Ponorogo from 1950 to 1980. In addition, this study also examines how Reog isused as an element in forming the image of Ponorogo City in the modern era. The problemsstudied in this study include: (1) How is Reog Ponorogo performing arts used to build theimage of Ponorogo City? (2) What is the relationship between Reog Ponorogo art and thepolitical and social context of its time? This study uses a qualitative approach with observationand interview methods conducted for four days in Ponorogo. The analysis was carried out byreviewing the image of the city presented through Reog art based on the perspective of thecommunity and visitors to Ponorogo City. The results of the study show that Reog Ponorogo isone of the main elements in building the identity of Ponorogo City, especially through theannual Grebeg Suro event that attracts domestic and foreign tourists. However, a paradox wasfound between the image of the city formed with the traditional meaning of Reog Ponorogo,where modern imagery is often not in line with the philosophical values contained in the arttradition
Keywords: reog ponorogo, performing arts, philosophy